Genetic and Environmental Influences on Autism Spectrum Disorder: A Multi-Center Study Exploring Gene-Environment Interactions and Biomarkers in Indonesia - Vita Amanda; Rashidah Unaib Al-Zayid; Winata Putri; Sonya Syarifah; Tiffany Gabriele; Leonardo Simanjuntak; Cinthya Callathea (Sriwijaya Journal of Neurology, 2023)
Introduction: Autism spectrum disorder (ASD) is a neurodevelopmental condition with a complex etiology involving genetic and environmental factors. This multi-center study investigated gene-environment interactions and potential biomarkers associated with ASD in the Indonesian population. Methods: Children diagnosed with ASD (n=500) and age-matched typically developing controls (n=500) were recruited across five major Indonesian cities. Whole-exome sequencing targeted genotyping, and environmental risk factor assessments were conducted. Biomarker analyses included cytokine levels, oxidative stress markers, and neurotransmitters. Results: Genetic analysis revealed both rare and common variants associated with ASD risk, including variants in CHD8, SCN2A, NRXN1, and novel genes. Prenatal exposures (maternal medication use, infections), perinatal complications (preterm birth, low birth weight), and postnatal factors (pesticide exposure, air pollution) were associated with increased ASD risk. Children with ASD exhibited elevated inflammatory markers (TNF-α, IL-6, IL-1β), increased oxidative stress (higher MDA, lower GSH), and altered neurotransmitter levels (lower serotonin and dopamine) compared to controls. Conclusion: This study provides insights into the interplay of genetic and environmental factors contributing to ASD risk in Indonesia. The identified genetic variants, environmental risk factors, and potential biomarkers may contribute to our understanding of ASD etiology and inform the development of targeted interventions and early detection strategies.